Exploring untapped energy potential of urban solid waste - Vaish B.; Srivastava V.; Singh P.; Singh A.; Singh P.K.; Singh R.P. (My University, 2025)
There is continuous increase in quantum and variety of waste being generated by anthropogenic activities. Burgeoning amount of waste being generated has potential to harm the environment and human health. Aggravating the problem, ever-increasing energy demand is putting strain on the non-renewable sources of energy and there is huge gap between the demand and supply of energy. This has led the scientific communities to adopt innovative methods to reduce, reuse and recycle them. Therefore, there is an urgent need to minimize the quantity of waste and meet the current demand profile of energy is required; technologies to recover energy from waste can play a vital role in substantial energy recovery and reduction in waste for final disposal; in addition to meet the rising energy requirement. Generating power from waste has greatly reduced the environmental impact and dependency on fossil fuels for electricity generation. Economically also it is an optimal solution for recovery of heat and power from waste. This paper gives an overview of energy potential stored in waste, major available waste-to-energy technologies and also strategic action plan for implementation of these technologies. © 2016, Joint Center on Global Change and Earth System Science of the University of Maryland and Beijing Normal University and Springer-Verlag Berlin Heidelberg.